ANALISIS BUKU TEKS CERDAS BERBAHASA INDONESIA UNTUK SMA/MA KELAS XI - Abdurrohman; sakrim (Jurnal Sastra Aksara, 2021)
Textbooks are teaching materials used as guidelines in teaching and learning activities. Textbooks are said to be handbooks or student and teacher guidelines that contain material that is in accordance with national education standards used to support teaching and learning activities in the classroom. Therefore, the textbooks used must meet the eligibility criteria according to the National Education Standards Agency. The feasibility of the textbook is seen from four aspects, namely the feasibility of the content, the feasibility of the language, the feasibility of the presentation, and the feasibility of the graphic. This study uses a qualitative method. Data collection methods used in this research are documentation and checklist techniques. The data analysis method used is a qualitative descriptive method, namely describing or describing the data that has been collected. The results of the study in this study illustrate that textbooks Bahasa Indonesia Ekspresi Diri Dan Akademik Kelas XI Kurikulum 2013 Published by Ministry of Education and Culture said to be worthy and in accordance with the National Education Standards Agency. However there is still a lack of some of the components found in the textbook Bahasa Indonesia Ekspresi Diri Dan Akademik Kelas XI Kurikulum 2013 Published by Ministry of Education and Culture.